EFFECT TWO ZERO DISPERSION WAVELENGTHS AND RAMAN SCATTERING IN THE THIRD-ORDER SOLITON OF SOLID CORE PHOTONIC CRYSTAL FIBERS TO PRODUCE SUPERCONTINUUM GENERATION - Altaie, Mohammed (Malaysian Journal of Science, 2022)
Photonic crystal fibers (PCFs) which consist of dielectric materials are a don't ever and an ever field in more modern application. The Split-Step Fourier method (SSFM) was used in this work to create a fiber photonic crystal, which was suggested and validated using a Matlab software .The impact of two -zero- dispersion on the Soliton in solid core photonic crystal fibers has been studied by investigating the interplay between Raman effect and second- order- dispersion. It has been discovered that the proposed photonic crystal fibers two –zero- dispersion wavelengths (TZDW) can be used to effectively tailor the properties of third order soliton. Many current applications, including medical and industrial, rely on spectral expansion. In addition, soliton has an important role in modern communication systems.